Cloning and Expression of Nano Body Gene against Enterotoxin B of Staphylococcus Aureus - Zahra Tavassoli; Hamideh Rouhani Nejad; Jalil Fallah Mehrabadi (Journal of Advanced Biomedical Sciences, 2016)
Background & Objectives: Staphylococcus aureus bacteria causes many different diseases by secretion of various enterotoxins. Therefore, it is necessary to develop ways that facilitate the detection of enterotoxins. Nowadays, immunochemical methods which are based on monoclonal antibody technology are used. The heavy chain antibodies that are called VHH or Nano body were found in blood serum of the Camelidae family. The unique properties of this antibody such as their binding to small molecules like toxins make them attractive candidates for the development of immunodiagnostic tests. The present study was done to achieve a VHH molecules against Staphylococcus enterotoxin B.